Greater Patient Satisfaction With Use of Nonabsorbable Sutures Compared to Absorbable Sutures for Skin Closure Following Knee Arthroscopy: A Randomized Controlled Trial - Adeeb Jacob Hanna, B.S; John Hayden Sonnier, M.D; Carlo Coladonato, M.S; Henson Destine, B.S; Sean Wilson, M.D; Michael G. Ciccotti, M.D; Fotios P. Tjoumakaris, M.D; Kevin B. Freedman, M.D (Elsevier, 2023)
Purpose: To evaluate patient outcomes and satisfaction after arthroscopic portal closure with absorbable versus nonabsorbable sutures after knee arthroscopy. Methods: Patients undergoing primary knee arthroscopy were identified during procedure scheduling. Exclusion criteria included revision procedures, concomitant ligament reconstruction, or meniscal repair surgery. Before surgery, enrolled patients were randomly assigned to undergo closure with either 3-0 Monocryl absorbable or 3-0 nylon non-absorbable sutures. Postoperative evaluation at 2, 6, and 12 weeks included a Visual Analogue Cosmesis scale, a 10-point visual analogue scale (VAS) for pain, patient scar assessment, and customized questionnaire assessing scar satisfaction. Results: Between January 2019 and August 2022, 247 were included for analysis: 145 in the absorbable group and 129 in the non-absorbable group. There was no significant difference between groups in terms of age, sex, body mass index, race, smoking status, or laterality of procedure. Patients in the nonabsorbable group reported higher overall satisfaction at week 6 follow-up (9.12 ± 1.85 vs 8.44 ± 2.49, P = .019) and week 12 follow-up (9.13 ± 1.76 vs 8.54 ± 2.50, P = .048). There was no difference in pain, swelling, itching, numbness, incisional pain, or burning at any time. Patients in the nonabsorbable group observed more skin discoloration at 2 weeks (3.00 ± 2.33 vs 2.41 ± 1.80, P = .026) and 6 weeks (3.74 ± 2.82 vs 2.98 ± 2.45, P = .032) follow-up with no significant difference at 12 weeks. Conclusion: In this study, patients were more satisfied with nonabsorbable sutures for portal wound closure after knee arthroscopy despite early reporting of increased skin discoloration relative to absorbable sutures. Level of Evidence: Level I, randomized controlled trial.